Rotary Screen Printed Metallization of Heterojunction Solar Cells: Toward High‐Throughput Production with Very Low Silver Laydown. Issue 8 (22nd June 2022) - Lorenz, Andreas; Klawitter, Markus; Linse, Michael; Ney, Linda; Tepner, Sebastian; Pingel, Sebastian; Sabet, Milad Salimi; Reiner, Julius; Oehrle, Katrin; Greutmann, Roland; Röth, Julius; Drews, Matthias; et al.
Abstract : Within this work, first bifacial silicon heterojunction solar cells with rotary screen printed front‐ and rear‐side metallization are demonstrated. The high‐throughput metallization process is carried out using an innovative rotary printing demonstrator machine with short process cycle times down to 0.65 s cell −1 . Furthermore, a very low total silver consumption of only 6–9 mg Wp −1 for the fully metallized bifacial silicon heterojunction solar cells is demonstrated. Using a newly developed screen simulation approach, the utilized fine line rotary and flatbed screens are analyzed regarding their suitability for fine line metallization and verified using in‐depth analysis of the geometrical and electrical properties of printed and cured metallization. The best group of fully rotary screen printed cells obtains a mean conversion efficiency of η RSP, avg  = 21.7% which is close to the flatbed screen printed reference group with η FSP, avg  = 22.1%. Using a hybrid approach with a rotary screen printed grid on the rear side and flatbed screen printed grid on the front side, a mean conversion efficiency of η hyb, avg  = 22.0% is obtained with a very low total silver consumption of only 9 mg Wp . Abstract : This work successfully demonstrates a high‐throughput rotary screen printing process for the metallization of silicon heterojunction (SHJ) solar cells. Silver paste laydown is reduced by up to 70% while maintaing a closely similar I–V performance of the SHJ cells to the reference. A substantial reduction of the cycle time per wafer compared to the reference process is demonstrated. Image of rotary screen and mesh with permission from Gallus Group.